Back to basics? The evolution of the subject of food security in the western world - Ferreiro, Maria de Fátima; Vale, S.; Sousa, C. (Winir 2023 Institutional innovation and and evolution changes to the modern world order, 2023)
Back to basics? the evolution of the subject of food security in the western world The reemergence of the concern with food safety at the beginning of the XXI century is an opportunity to reflect on the evolution of the concept and its normative approach (e.g. Law, public policies). The presentation is based on the assumption that we are assisting to a shift regarding the role of basic sectors, as it is the case of food system, in our societies. The change is related with systemic crisis we are dealing with and, thus, with the need to provide essential goods and services within sustainable approaches. The research considers the milestones of the evolution of food security concept, the main characteristics of global food economy, and the main trends of value chains and business models in this sector, such as the importance of local and seasonal production, and short supply chains. The European case will be mentioned as an illustration of the above trends and characteristics.